Strategy Analysis of Students Overcoming Insomniain “New Normal Era” After Pandemi - Ningsih, Wahyu Mustika; Hairina, Yulia; Fadhila, Mahdia (PROCEEDING SERIES OF PSYCHOLOGY, 2024)
With the return of changes to the learning system in the new normal era, this requires students to return to adapt to old habits. Of course this has an impact on the students themselves, one of which is the incidence of insomnia. The purpose of the research to strategy analyze of students overcoming insomnia in “new normal era” after pandemic. This research used qualitative methods with a phenomenological approach. Research subjects were selected by purposive sampling method as many as 3 students who experience insomnia. The analysis technique uses the Miles and Huberman model, namely after collecting data, data reduction, data display, and then verification or drawing conclusions will be carried out. The results of the analysis show that the strategies used by Banjarmasin students to overcome insomnia are classified into several themes, namely physical activity, relaxation activities, sleep hygiene, and religious activities. The conclusion is insomnia was due to several underlying factors, including changes in the learning system in the normal. Not only that, several internal and external factors cause it. Of course, this has an impact on aspects of student life, so they need to carry out certain strategies to overcome this.